Letter (copy) : Relief for Spain - Tewson, Vincent
012a-0011-001 International HVT/WJB/AC/100 24th November, 1938. Mr. Thomes McKenna, The National Union of Blastfurnacemen, Ore Miners, Coke Workers and Kindred Trades, 9 Borough Road West, Middlesbrough Dear Mr. McKenna, RELIEF FOR SPAIN. In reply to your letter of 22nd instant, the National Council of Labour are, of course, continuing their efforts to obtain contributions for the International Solidarity Fund, so that further assistance may be rendered to the Spanish workers. In this year's Report of the General Council, you will find full particulars of what has been done. At the close of Congress, arrangements were made immediately for sending further shipments of food. Last Tuesday, representatives of the Spanish T.U.C. called upon the National Council of Labour at Transport House, and expressed their thanks for the work we are doing, also the gratification of the Spanish people to those British sailors who were facing the blockade in order to carry supplies of foodstuffs into Spanish Government ports. As regards belligerent rights, you will have read in to-day's "Daily Herald" the telegram we sent yesterday to the Prime Minister in Paris. It is intended later to request him to receive a deputation when he returns, in regard to the removal of the ban on arms. Tomorrow (Friday) and Saturday, the Executives of the I.F.T.U. and the L.S.I. are meeting in Paris in order to decide on measures to be taken internationally, with a view to safeguarding the interests of the Spanish Government. Yours faithfully, Assistant Secretary 292/946/12a/11